Impacto emocional en cuidadores de niños con cáncer en el Hospital Oncológico Solca-Loja 2016-2017. - Matute Salazar, Jenner Alexander (2017)
Emotional imbalance is a comorbid condition, a syndrome that in addition of incapacitating approximately affects from 15 to 25% of cancer patients. The present research work is descriptive, which it was done in order to determine the emotional impact on children's caregivers with cancer, it is known that having a child with this diagnosis wakes up a lot of depersonalization in the caregiver creating wrong ideas and generating negative emotions around the prognosis of the disease. For this reason it seeks itself to identify the negative and positive emotions that are generated in the caregiver.The same that was achieved with the application of a test that seeks to know what type of emotions generates to a greater degree the caregiver describing multiple of them. As a result it was obtained itself that 85.5% of caregivers surveyed belong to female sex who are in an age range from 41 to 50 years, .in addition to this the negative emotions that prevailed were anxiety with 3.27%, fear with 4.73 and guilt with 4.18% the same ones that appeared to a great measurement during the diagnostic phase. Once the treatment was explained and already taken, more positive emotions were generated within which love predominated with 8.0%, inspiration with 7.64%, pride 6.0%, joy with 5.27% and gratitude with 4.91%. Given this, it can be affirmed that most of the generated questions correspond to the generation of positive emotions, this in front of the negative emotions that are generated in smaller proportion. Key words Fridrickson scale, negative emotions, positive emotions, antineoplastic treatment